SPICATIC ACID: A 4-CAROXYGENTISIC ACID FROM A GENTIANA SPICATA EXTRACT WITH POTENTIAL HEPATOPROTECTIVE ACTIVITY - Ayoub, N. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Investigation of the protective mechanisms of the aqueous alcoholic extract of Gentiana spicata (Gentianaceae) in carbon tetrachloride intoxicated rats was undertaken. Rats were treated with carbon tetrachloride at a dose of 1 ml/kg body weight intraperitoneally once every 24 hrs for 14 days. The hepatoprotective activity of the extract of Gentiana spicata was evaluated by measuring levels of serum marker enzymes, alanine aminotransferase (ALT) and aspartate aminotransferase (AST). Administration of the extract (250 mg/kg, b.wt.) significantly (p < 0.05) prevented CCl4-induced elevation of levels of serum AST and ALT. Treatment of rats with CCl4 led to a marked increase in lipid peroxidation as measured by malondialdehyde (MDA). This was associated with a significant reduction of the hepatic antioxidant system e.g. reduced glutathione (GSH). These biochemical alterations resulting from CCl4 administration were significantly (p < 0.05) inhibited by pretreatment with the extract of Gentiana spicata. These results suggest that the aqueous alcoholic extract of Gentiana spicata may act as a hepatoprotective and antioxidant agent. Phytochemical studies demonstrated a high phenolic content and led to the isolation and identification of the new carboxygentisic acid, 1,4-dicarboxy 2,5-dihydroxybenzene, for which we suggest the name spicatic acid, together with the two known flavonoids, quercetin 3-O-[(2,3,4-triacetyl-a-rhamnopyranosyl)-1”’6”]-3-acetyl-galactopyranoside and quercetin 3-O-[(2,3,4-triacetyl-a-rhamnopyranosyl)-1”’6”]-4-acetyl-galactopyranoside. All structures were elucidated on the basis of conventional analytical methods and confirmed by high resolution FTMS, 1D- and 2D-NMR data. The new phenolic carboxylic acid, spicatic acid, is of special interest as it represents the first phenolic acid which bears two carboxyl functions in one aromatic ring.